Determination of Fatty Acids in Plant Seeds of Leguminosae Family from Arid Zone of Rajasthan - Arora, Arun; Sen, Rajendra (Asian Journal of Chemistry, 2010)
Some fatty acids viz., palmitic acid, oleic acid, linoleic acid and linolenic acid in three plant seeds were determined. The plant seeds samples analyzed were Acacia nilotica, Cassia fistula, Tamarindus indica. All samples were collected from arid zone of Rajasthan and have been identified and studied for their component fatty acids using TLC and HPLC techniques. Physicochemical characteristics were determined by standard AOCS methods. The fatty acids were analyzed by high performance liquid chromatography with μBondapak C-18 column and UV/ VIS. detector. The omega-6 or linoleic acid was found the highest value in Tamarindus indica and Cassia fistula. The palmitic acid, oleic acid and linolenic acids were also found in all samples.